Control of the metallurgical processing of ICDP cast irons - Hampl, Jiří (Materiali in tehnologije, 2014)
The article is focused on the use of the measurement of oxygen activity for the management of cast-iron metallurgical processing in the operating conditions of a centrifugal-roll casting foundry. The paper presents the results of the oxygen-activity measurement recorded during the metallurgical processing of cast iron from the beginning of the melting to the inoculation of cast iron. The measurement of oxygen activity was made with specifically developed devices and the probes with a high sensitivity designed for measuring aO in cast iron by Heraeus Electro-Nite Celox Foundry. The oxygen activities in cast iron correlate with the properties of cast iron.
Keywords: cast iron; lito železo; oxygen activity; aktivnost kisika; ICDP iron; ICDP-železo; inoculation; inokulacija